Avaliação agronômica de variedades de alface em cultivo em sistema DFT (Deep Film Technique) - Silveira, Thiago Rodrigues (Universidade Federal de São Carlos, 2023)
Lettuce (Lactuca sativa L.) is considered the most commercialized and consumed leafy vegetable by Brazilians, and can be produced all year round. Hydroponic cultivation is an affordable alternative to conventional cultivation. The most widespread hydroponic cultivation is cultivation in an NFT system. Other forms of hydroponic cultivation have not yet been well adapted to the economic/social and environmental particularities of Brazil. The NFT system still has a bottleneck with great environmental impact, which consists of the short life of the nutrient solution and the need for its disposal and renewal. Hydroponic cultivation in a DFT system corresponds to cultivation in a system with a deep layer of nutrient solution, in which the roots are completely submerged and the recirculation of the solution is minimal. The DFT cultivation system is widespread in European countries, places with less availability of quality water resources for use in agriculture. This system requires a greater volume of nutrient solution per number of plants, a characteristic that gives the solution a high buffering power and allows it to be maintained for a longer period of time through specific nutritional replacements. In this way, the objective was to evaluate the cultivation of 3 varieties of lettuce, Natália RZ (smooth lettuce), Tudela RZ (mini romaine lettuce) and Carmolí RZ (purple curly lettuce), in a DFT system, evaluating agronomic and commercial characteristics after -harvest, and the behavior of nutritional parameters, Electrical Conductivity, pH, Temperature and Oxygenation of the nutrient solution throughout the experiment. The agronomic evaluation was carried out by submitting the averages of Fresh Mass of Aerial Part, Fresh Mass of Roots, Total Fresh Mass, Length of Roots, Length of Aerial Part, Total Length and Number of leaves, to the Scott-Knott test at 5%. The commercial evaluation was carried out at the Verdureira® company's processing unit, based on processing and quality control parameters. The nutritional solution behavior data were carried out through laboratory analyzes collected every 7 days, and on-site measurements, carried out daily, twice a day. The Natália RZ lettuce variety stood out in the averages of Total Fresh Mass, Fresh Aerial Mass, Root Length and Total Length. The Tudela RZ variety stood out in the averages of Fresh Root Mass and Number of Leaves. The Carmolí RZ variety stood out in the Aerial Part Length averages. The evaluation commercial presented higher final product utilization values ​​than those obtained in the NFT system. The behavior of the nutrient solution demonstrated significant consumption of Calcium and Potassium, and increased levels of Ammonia Nitrogen. The system showed promise for growing vegetables in the face of the obstacles of the NFT system.
Agronomic evaluation of lettuce varieties grown in DFT system (Deep Film Technique)
Keywords: Alface; Olericultura; São Roque; DFT; Hidroponia; Lettuce; Horticulture; Hydroponics; CIENCIAS AGRARIAS::AGRONOMIA